Calcio-herbal formulation, Divya-Swasari-Ras, alleviates chronic inflammation and suppresses airway remodelling in mouse model of allergic asthma by modulating pro-inflammatory cytokine response - Acharya Balkrishna (Biomedicine & Pharmacotherapy, 2020)
Asthma is a chronic allergic respiratory disease with limited therapeutic options. Here we validated the potential anti-inflammatory, anti-asthmatic and immunomodulatory therapeutic properties of calcio-herbal ayurvedic formulation, Divya-Swasari-Ras (DSR) in-vivo, using mouse model of ovalbumin (OVA) induced allergic asthma. HPLC analysis identified the presence of various bioactive indicating molecules and ICP-OES recognized the presence of Ca mineral in the DSR formulation. Here we show that DSR treatment significantly reduced cardinal features of allergic asthma including inflammatory cell accumulation, specifically lymphocytes and eosinophils in the Broncho-Alveolar Lavage (BAL) fluids, airway inflammation, airway remodelling, and pro-inflammatory molecules expression. Conversely, number of macrophages recoverable by BAL were increased upon DSR treatment. Histology analysis of mice lungs revealed that DSR attenuates inflammatory cell infiltration in lungs and thickening of bronchial epithelium. PAS staining confirmed the decrease in OVA-induced mucus secretion at the mucosal epithelium; and trichrome staining confirmed the decrease in peribronchial collagen deposition upon DSR treatment. DSR reduced the OVA-induced pro-inflammatory cytokines (IL-6, IL-1β and TNF-α) levels in BALF and whole lung steady state mRNA levels (IL-4, -5, -33, IFN-γ, IL-6 and IL-1β). Biochemical assays for markers of oxidative stress and antioxidant defence mechanism confirmed that DSR increases the activity of SOD, Catalase, GPx, GSH, GSH/GSSG ratio and decreases the levels of MDA activity, GSSG, EPO and Nitrite levels in whole lungs. Collectively, present study suggests that, DSR effectively protects against allergic airway inflammation and possess potential therapeutic option for allergic asthma management.